2012
DOI: 10.1155/2012/264035
|View full text |Cite
|
Sign up to set email alerts
|

A Single Platinum Microelectrode for Identifying Soft Drink Samples

Abstract: Cyclic voltammograms recorded with a single platinum microelectrode were used along with a non-supervised pattern recognition, namely, Principal Component Analysis, to conduct a qualitative analysis of sixteen different brands of carbonated soft drinks (Kuat, Soda Antarctica, H2OH!, Sprite 2.0, Guarana Antarctica, Guarana Antarctica Zero, Coca-Cola, Coca-Cola Zero, Coca-Cola Plus, Pepsi, Pepsi Light, Pepsi Twist, Pepsi Twist Light, Pepsi Twist 3, Schin Cola, and Classic Dillar’s). In this analysis, soft drink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Three-dimensional PCA scores of the binding data described by Takeuchi et al revealed that a clear protein distinction was possible and that protein-imprinted polymer arrays can be applied to protein profiling by pattern analysis of binding activity for each polymer [19][20][21]. PCA has also been used in conjunction with electrochemical methods such as cyclic voltammetry [16,17,[22][23][24][25]. An attractive approach for the development of biochemical sensors would be the integration of smart materials (e.g., MIPs) with said electrochemical techniques This paper demonstrates the use of pattern recognition techniques to uniquely identify fingerprint profiles for four different proteins by coupling electrochemical sensor strategies with hydrogel-based MIPs.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional PCA scores of the binding data described by Takeuchi et al revealed that a clear protein distinction was possible and that protein-imprinted polymer arrays can be applied to protein profiling by pattern analysis of binding activity for each polymer [19][20][21]. PCA has also been used in conjunction with electrochemical methods such as cyclic voltammetry [16,17,[22][23][24][25]. An attractive approach for the development of biochemical sensors would be the integration of smart materials (e.g., MIPs) with said electrochemical techniques This paper demonstrates the use of pattern recognition techniques to uniquely identify fingerprint profiles for four different proteins by coupling electrochemical sensor strategies with hydrogel-based MIPs.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach, electrochemical techniques are relatively easy to operate, allow the use of low-cost materials for the fabrication of sensors, and enable quantification and discrimination between samples in a short time, without the necessity to circumvent the problems reported for optical and colorimetric techniques. The use of electrochemical sensors has been previously reported for food and beverage analysis [30][31][32][33]. We now demonstrate the fabrication of an array of electrochemical sensors that, with the aid of chemometric tools (electronic tongue) [34], are able to distinguish between unadulterated milk samples and those containing urea, formaldehyde or melamine contaminants.…”
Section: Introductionmentioning
confidence: 84%